Tashmim Kitab Al-Jaib “Dhiya’ul Muta’allimin” Li Muhadatsah Al-Thullab Fi Al-Ma’had Al-Islamiyah Al-Hasaniyah Ponorogo - Tricahyo, Agus; Mukaromah, Muhimmatul; Wahidah, Zulvata Kholifatul (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
This study aims to determine the design of the Muhadatsah book and the effectiveness of its use at Al-Hasanah Islamic Boarding School. This study uses the Research and Development (R&D) method and data collection using observation, interviews, questionnaires, and tests. The test subjects consisted of material experts, learning design experts, linguists, and 3rd-grade students of Al-Hasanah Islamic boarding school as the target of testing the Arabic conversation product dhiyaul muta'alimin. The results of this study show: 1) The product designed is an Arabic conversation pocket book,